Characterisation of chemical component migration in automotive paint by synchrotron infrared imaging - Maric, Mark; van Bronswijk, Wilhelm; Lewis, Simon; Pitts, K.; Martin, D. (Elsevier Ireland Ltd, 2013)
Synchrotron infrared chemical imaging was employed to examine and assess the extent of interlayer component migration within multilayer automotive paint samples, with a particular emphasis on the cross-linking additive melamine. Two dimensional infrared chemical images revealed that melamine consistently diffuses in select paint samples from the underlying basecoat into the outermost clear coat layer. Pigments from the basecoat were also found to migrate into the adjoining layers. This is significant as the relative abundance of both melamine and pigments will vary greatly depending upon the region of the layer analysed. This component migration will undoubtedly impact the information gleaned from a questioned sample via library searching software or multivariate statistics. As a result, appropriate analytical protocols will need to be utilised to mitigate the effects of interlayer pigment and melamine diffusion, so as to afford a true representation of the composition of the coating for forensic identification purposes.